Phase-shift photomask blank and phase-shift photomask

By designing a specific phase shift film layer structure in a phase shift photomask and controlling the content ratio of transition metal and silicon, the problem of insufficient phase shift film thickness in the prior art is solved, and the phase shift and high transmittance of the film are achieved, and the miniaturization and accuracy of the pattern are improved.

CN110955109BActive Publication Date: 2025-04-22SHIN ETSU CHEMICAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201910914432.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-26
Filing Date
2019-09-26
Publication Date
2025-04-22
Estimated Expiration
2039-09-26

AI Technical Summary

Technical Problem

In semiconductor manufacturing, it is difficult to achieve a thin enough phase shift film in existing phase shift type photomasks, while meeting the requirements of phase shift and transmittance, resulting in challenges in miniaturization of patterns and improving accuracy.

Method used

By designing a phase shift film consisting of a single or multiple layers including a layer composed of transition metal, silicon, nitrogen and oxygen, and a layer composed of silicon, nitrogen and oxygen, the ratio of the total content of transition metal to transition metal and silicon is controlled to be less than 0.03, and the thinning of the phase shift film is achieved while ensuring the need for phase shift and transmittance.

Benefits of technology

The thinning of the phase shift film is achieved, the miniaturization and accuracy of the pattern is improved, and the demand for higher accuracy and more detailed patterns in lithography technology is met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110955109B_ABST
    Figure CN110955109B_ABST
Patent Text Reader

Abstract

The present invention provides a phase-shift photomask blank and a phase-shift photomask. Specifically, a phase-shift photomask blank is provided, which includes a transparent substrate and a phase-shift film thereon, the phase-shift film is composed of a single layer or a multilayer, the single layer or the multilayer includes at least one layer selected from a layer composed of a transition metal, silicon, nitrogen and oxygen and a layer composed of silicon, nitrogen and oxygen, the phase shift of the phase-shift film is 150° to 250° for light with a wavelength of 200 nm or less, the transmittance is 60% to 80%, the thickness of the phase-shift film is 150 nm or less, and the content (atomic ratio) of the layer composed of the transition metal, silicon, nitrogen and oxygen as a ratio of the transition metal to the total content of the transition metal and silicon is 0.03 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This nonprovisional application claims priority under 35 USC §119(a) to Patent Application No. 2018-180590 filed in Japan on September 26, 2018, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present invention relates to a phase-shift photomask blank and a phase-shift photomask, which are generally used for manufacturing semiconductor integrated circuits. Background Art

[0004] In the field of semiconductor technology, research and development of pattern miniaturization is further underway. In particular, with the progress of integration of large-scale integrated circuits in recent years, the trend of miniaturization of circuit patterns, finer interconnection patterns, and contact hole patterns for interlayer connections of battery formation has accelerated, generating further demand for fine processing technology. In this case, in the technical field of manufacturing photomasks for photolithography processes in fine processing, there is a growing demand for the development of technologies for forming finer and more accurate circuit patterns (mask patterns).

[0005] Reduced projection is the most typical method of forming a pattern on a semiconductor substrate using photolithography. For this purpose, the size of the pattern on the photomask is about four times the size of the pattern to be drawn on the semiconductor substrate. Currently, in the field of photolithography, the size of the circuit pattern to be drawn is much smaller than the wavelength of the light used for exposure. Therefore, if the photomask pattern is simply formed as a four-fold magnification of the circuit pattern, the original pattern of the photomask cannot be accurately transferred to the resist film on the semiconductor substrate because the light interference caused in the exposure affects the transfer.

[0006] Therefore, in some cases, the pattern formed on the photomask is formed more complex than the actual circuit pattern to alleviate this effect of light interference. The pattern shape for this purpose can be exemplified by a shape in which optical proximity correction (OPC) is applied to the actual circuit pattern. For pattern miniaturization and enhanced accuracy, improved illumination, immersion lithography and resolution enhancement technology (RET) and double patterning lithography are used.

[0007] As one of the resolution enhancement techniques (RET), a phase shift method is used. The phase shift method is a contrast enhancement method by utilizing light interference caused by a film pattern formed in a photomask and capable of reversing a phase by about 180°. A halftone phase shift type photomask is one of the photomasks adopting this method. The halftone phase shift type photomask includes a transparent substrate made of quartz or the like that is transparent to exposure light, and a mask pattern formed thereon and made of a halftone phase shift film that is capable of reversing a phase by about 180° and has a transmittance that is insufficient to facilitate pattern formation. Exemplary halftone phase shift type photomasks that have been proposed include a halftone phase shift film composed of molybdenum silicon oxide (MoSiO) or molybdenum silicon oxynitride (MoSiON) (JP-A H07-140635 (Patent Document 1)).

[0008] Citation List

[0009] Patent Document 1: JP-A H07-140635

[0010] Patent Document 2: JP-A 2007-33469

[0011] Patent Document 3: JP-A 2007-233179

[0012] Patent Document 4: JP-A-2007-241065 Summary of the invention

[0013] The transmittance of a phase shift film is usually below 20%, typically about 6% transmittance, however, recent research also involves higher transmittances. Films with high transmittance also have a high light attenuation effect due to interference, which is beneficial for fine patterning in some cases. In order to manufacture a phase shift type photomask blank with high transmittance, a high oxygen content is required to increase the transmittance. However, although a higher oxygen content can increase the transmittance, a higher oxygen content causes problems, such that the refractive index of the film is reduced, and a larger film thickness is required to obtain a predetermined phase shift. The phase shift film is preferably thinner, because not only is the thin film beneficial for patterning, but the thin film can also reduce the three-dimensional effect. Therefore, in photolithography, a thinner film is required to form a finer pattern.

[0014] The present invention is made to solve the above problems and provides a phase shift type photomask blank and a phase shift type photomask having a thin phase shift film that meets the requirements of pattern miniaturization, the phase shift film is advantageous in patterning and reducing three-dimensional effects, and meets the necessary phase shift and transmittance of the phase shift film.

[0015] The inventors first studied the commonly used phase shift film containing transition metals such as molybdenum, in order to seek to develop a phase shift film that is thin but satisfies the phase shift and transmittance necessary for the phase shift film. A phase shift film having a transmittance of 60% or more for light with a wavelength of 200 nm or less will have a lower transmittance even if a small amount of transition metal is added. Adding a larger amount of oxygen (which is intended to compensate for the reduced transmittance thus) results in a decrease in the refractive index of the film at the required transmittance as the amount of oxygen added increases. Therefore, in order to satisfy the phase shift necessary for the phase shift film in this case, the thickness of the film must be increased.

[0016] The inventors have found that when the phase shift film is constructed of a single layer or a multilayer including at least one layer selected from a layer composed of a transition metal, silicon, nitrogen and oxygen and a layer composed of silicon, nitrogen and oxygen, and the content ratio (atomic ratio) which is the ratio of the transition metal to the total content of the transition metal and silicon is 0.03 or less, even if the phase shift film is designed so that the phase shift is 150° to 250° and the transmittance is 60% to 80% for light with a wavelength of 200 nm or less, the phase shift film can be thinned to 150 nm or less.

[0017] In one aspect, the present invention provides a phase-shift photomask blank, comprising a substrate and a phase-shift film thereon, wherein the phase-shift film is composed of a single layer or multiple layers, wherein the single layer or multiple layers include at least one layer selected from a layer composed of a transition metal, silicon, nitrogen and oxygen and a layer composed of silicon, nitrogen and oxygen, wherein:

[0018] For light with a wavelength of 200nm or less, the phase shift of the phase shift film is 150° to 250°, the transmittance is 60% to 80%, the thickness is 150nm or less, and,

[0019] The content (atomic ratio) of the layer composed of transition metal, silicon, nitrogen and oxygen, which is the ratio of the transition metal to the total content of the transition metal and silicon, is 0.03 or less.

[0020] Preferably, the phase shift film includes a layer composed of transition metal, silicon, nitrogen and oxygen, and the content (atomic ratio) of the layer composed of transition metal, silicon, nitrogen and oxygen as a ratio of transition metal to the total content of transition metal and silicon is 0.001 or more.

[0021] Preferably, the total content of nitrogen and oxygen in each layer constituting the phase shift film is 50 at % or more, and / or the nitrogen content is 10 at % or more, and the nitrogen content is lower than the oxygen content in the layer.

[0022] Preferably, the transition metal comprises molybdenum.

[0023] Preferably, the phase-shift photomask blank further comprises a second layer consisting of a single layer or a plurality of layers on the phase-shift film, the second layer being composed of a chromium-containing material.

[0024] In another aspect, the present invention provides a phase shift type photomask prepared by using a phase shift type photomask blank.

[0025] Beneficial Effects of the Invention

[0026] According to the present invention, a phase-shift photomask blank and a phase-shift photomask are provided, which have a thinner phase-shift film which is advantageous in patterning and exposure and have a satisfactory phase shift and high transmittance necessary for the phase-shift film. The phase-shift photomask of the present invention allows exposure that meets the requirements for further miniaturization and higher-precision patterning in lithography. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A and 1B are cross-sectional views illustrating an exemplary phase-shift photomask blank and a phase-shift photomask of the present invention.

[0028] Figure 2 A to 2C are cross-sectional views illustrating other examples of the phase shift type photomask blank of the present invention. DETAILED DESCRIPTION

[0029] The phase-shift photomask blank of the present invention includes a transparent substrate such as a quartz substrate, and a phase-shift film disposed on the transparent substrate and consisting of a single layer or multiple layers (i.e., two or more layers). The phase-shift photomask of the present invention includes a transparent substrate such as a quartz substrate, and a mask pattern (photomask pattern) of the phase-shift film disposed on the transparent substrate and consisting of a single layer or multiple layers (i.e., two or more layers).

[0030] The transparent substrate in the present invention is preferably, for example, a 6-inch square, 25-mil thick transparent substrate, referred to as a 6025 substrate specified by the SEMI standard, which is usually represented by a 152 mm square, 6.35 mm thick transparent substrate according to the SI unit system.

[0031] Figure 1 A is a cross-sectional view illustrating an exemplary phase shift type photomask blank of the present invention. In this embodiment, a phase shift type photomask blank 100 includes a transparent substrate 10 and a phase shift film 1 formed on the transparent substrate 10. Figure 1 B is a cross-sectional view illustrating an exemplary phase shift type photomask of the present invention. In this embodiment, the phase shift type photomask 101 includes a transparent substrate 10 and a phase shift film pattern 11 formed on the transparent substrate 10.

[0032] The phase shift film may be composed of a single layer designed to satisfy the necessary phase shift and transmittance of the phase shift film. The phase shift film is also preferably composed of a plurality of layers including, for example, a layer having an antireflection function satisfying the required surface reflectivity, so that the phase shift film as a whole satisfies the necessary phase shift and transmittance.

[0033] In both the case of a single layer and a multilayer, each layer may be formed to have a composition that continuously changes in the thickness direction. In the case where the phase shift film is composed of a plurality of layers, the layers may be a combination of at least two layers selected from layers having different constituent elements and layers having the same constituent elements but having different composition ratios. In the case where the multilayer includes at least three layers, when the layers are not adjacent to each other, the same layers may be combined.

[0034] The phase shift film in the present invention is composed of a single layer or a multilayer, and the single layer or the multilayer includes at least one layer selected from a layer composed of a transition metal, silicon, nitrogen and oxygen and a layer composed of silicon, nitrogen and oxygen. The layer composed of a transition metal (Me), silicon (Si), nitrogen (N) and oxygen (O) is preferably a layer basically composed of only these four elements (except for inevitable impurities). At the same time, the layer composed of silicon (Si), nitrogen (N) and oxygen (O) is preferably a layer basically composed of only these three elements (except for inevitable impurities). Specifically, MeSiNO (transition metal silicon oxynitride) layer and SiNO (silicon nitride oxide) layer are exemplified. It is worth noting that MeSiNO and SiNO only represent the constituent elements, not the composition ratio of the constituent elements. Examples of transition metals include molybdenum, zirconium, tungsten, titanium, hafnium, chromium and tantalum, and the transition metal is preferably molybdenum. In particular, the transition metal is preferably molybdenum.

[0035] The content ratio (atomic ratio) of the transition metal to the total content of the transition metal and silicon in the layer composed of transition metal, silicon, nitrogen and oxygen is preferably 0.03 or less, more preferably 0.02 or less. As for the layer composed of silicon, nitrogen and oxygen, the content ratio (atomic ratio) of the transition metal to the total content of the transition metal and silicon is 0 (zero). The phase shift film more preferably includes at least one layer composed of transition metal, silicon, nitrogen and oxygen. In this case, the content ratio (atomic ratio) of the transition metal to the total content of the transition metal and silicon is preferably 0.001 or more, more preferably 0.003 or more. By controlling the content ratio of the transition metal to the total content of the transition metal and silicon within the above preferred range, the problem of pattern size change or degradation in the layer containing transition metal and silicon can be improved.

[0036] When the phase shift film in the present invention is composed of a single layer, the silicon content in the entire single layer; when the phase shift film is composed of a plurality of layers, the silicon content in one or more layers of the plurality of layers; in particular, when the phase shift film is provided with an oxidized surface layer, the silicon content in each of the plurality of layers except the oxidized surface layer described below is preferably 30 at % or more, more preferably 35 at % or more, and preferably 45 at % or less, more preferably 40 at % or less.

[0037] When the phase shift film in the present invention is composed of a single layer, in the entirety of such a single layer; when the phase shift film is composed of a plurality of layers, in one or more layers of such a plurality of layers; in particular, when the phase shift film is provided with an oxidized surface layer, in each of the plurality of layers except for the oxidized surface layer described below, the nitrogen content is preferably 10 at % or more, more preferably 13 at % or more, and preferably 30 at % or less, more preferably 20 at % or less, or the oxygen content is preferably 60 at % or less, more preferably 50 at % or less.

[0038] When the phase shift film in the present invention is composed of a single layer, in the entirety of such a single layer; when the phase shift film is composed of a plurality of layers, in one or more layers of such a plurality of layers; in particular, when the phase shift film is provided with an oxidized surface layer, in each of the plurality of layers except the oxidized surface layer described below, the total content of nitrogen and oxygen is preferably 50 at % or more, more preferably 60 at % or more, or the nitrogen content is preferably lower than the oxygen content.

[0039] When the phase shift film in the present invention is composed of a single layer, in the entirety of such a single layer; when the phase shift film is composed of a multilayer, in one or more layers of such a multilayer; in particular, when the phase shift film is provided with an oxidized surface layer, in each layer of the multilayer except the oxidized surface layer described below, the ratio of silicon to nitrogen (silicon / nitrogen) is preferably 3 / 1 to 4 / 1 (atomic ratio).

[0040] The phase shift film of the present invention having a predetermined thickness has a predetermined phase shift amount (phase shift) and predetermined transmittance for light having a wavelength of 200 nm or less (exposure light), particularly ArF excimer laser light (193 nm) used for photolithography through a phase shift type photomask.

[0041] As a result of the phase shift caused by the interference of the exposure light passing through each area, the phase shift of the exposure light passing through the phase shift film in the present invention can be sufficient to increase the contrast at the boundary between the area with the phase shift film (phase shift area) and the area without the phase shift film. The phase shift can be 150° or more, preferably 170° or more, and 250° or less, preferably 230° or less. Although most common phase shift films adopt a phase shift of about 180°, from the viewpoint of increasing the contrast, the phase shift is not limited to about 180°. For light (exposure light) with a wavelength of 200nm or less, especially ArF excimer laser (193nm), the phase shift film in the present invention can have a phase shift amount controlled within the above range. At the same time, the transmittance of the phase shift film in the present invention for the exposure light can be a high transmittance of 60% to 80%, which is different from the usual transmittance in the prior art.

[0042] When the overall thickness of the phase shift film is thin, a fine pattern can be easily formed. Therefore, the total thickness of the phase shift film in the present invention is 150 nm or less, preferably 130 nm or less. Meanwhile, the lower limit of the thickness of the phase shift film can be set as long as the desired optical properties can be obtained using exposure light, and is generally 50 nm or more, but is not limited thereto.

[0043] The phase shift film in the present invention, when composed of a single layer, in the entirety of such a single layer; when the phase shift film is composed of a multilayer, in one or more layers of such a multilayer; in particular, when the phase shift film is provided with an oxidized surface layer, in the entirety of the multilayer except for the oxidized surface layer described below, its refractive index n for exposure light is preferably 1.75 or more, more preferably 1.8 or more. In the case where the oxygen content of the phase shift film is controlled to be less than 60at%, especially less than 50at%, or in the case where the transition metal content is reduced, the phase shift film can have a prescribed transmittance and an increased refractive index, and can also have a thinner thickness, satisfying the necessary phase shift of the phase shift film. When the oxygen content is low, the refractive index is high, and the high refractive index helps to obtain a thinner film with a desired phase shift.

[0044] The phase shift film of the present invention has an extinction coefficient k for exposure light greater than 0 (zero), preferably less than 0.1, and more preferably less than 0.05, in the entire single layer when composed of a single layer; or in the entire multilayer when composed of a multilayer.

[0045] The phase shift film in the present invention can be formed by a known film forming method. The phase shift film is preferably formed by sputtering, by which a highly uniform film can be easily obtained, and the sputtering can be DC sputtering or RF sputtering. The target and sputtering gas are appropriately selected according to the type and composition of the layer to be formed. Examples of targets include silicon targets, silicon nitride targets, and targets containing both silicon and silicon nitride. These targets may contain oxygen. For phase shift films containing transition metals, these targets may contain transition metals. In the case of phase shift films containing transition metals, targets containing transition metals and targets not containing transition metals may be used simultaneously. In the case of appropriately controlling the feed amount, the nitrogen content and oxygen content may be controlled by reactive sputtering using any reactive gas such as nitrogen-containing gas, oxygen-containing gas, and nitrogen- and oxygen-containing gas. In particular, nitrogen (N2 gas), oxygen (O2 gas), and nitrogen oxide gas (N2O gas, NO gas, and NO2 gas) may be used as reactive gases. Rare gases such as helium, neon, and argon may also be used as sputtering gases.

[0046] In order to suppress changes in the properties of the phase shift film, the phase shift film composed of a plurality of layers may include an oxidized surface layer formed as the outermost layer on the top surface (on the side away from the transparent substrate). The oxygen content of the oxidized surface layer may be 20 at% or more, preferably 50 at% or more. Examples of methods for forming the oxidized surface layer specifically include atmospheric oxidation (natural oxidation); and forced oxidation treatment such as treating the sputtered film with ozone gas or ozone water, or heating to 300°C or more in an oxygen-containing atmosphere such as an oxygen atmosphere by heating in an oven, lamp annealing or laser heating. The thickness of the oxidized surface layer is preferably 10 nm or less, more preferably 5 nm or less, and most preferably 3 nm or less. The effect of the oxidized surface layer can generally be obtained with a thickness of 1 nm or more. Although the oxidized surface layer can be formed by sputtering under an increased amount of oxygen, it is more preferred to form the oxidized surface layer by the above-mentioned atmospheric oxidation or oxidation treatment in terms of obtaining a layer with fewer defects.

[0047] The phase-shift photomask blank of the present invention may include a second layer consisting of a single layer or multiple layers and formed above the phase-shift film. The second layer is usually arranged adjacent to the phase-shift film. Specific examples of the second layer are a light-shielding film, a combination of a light-shielding film and an anti-reflection film, and a processing auxiliary film that acts as a hard mask in the process of patterning the phase-shift film. In the case of using a third layer as described below, the second layer can be used as a processing auxiliary film that acts as an etching stop layer (etching stop film) in the process of patterning the third layer. The material of the second layer is preferably a chromium-containing material.

[0048] pass Figure 2 This embodiment will be specifically described using the phase shift type photomask blank exemplified in A. Figure 2 A is a cross-sectional view illustrating an exemplary phase shift type photomask blank of the present invention. In this embodiment, the phase shift type photomask blank 100 includes a transparent substrate 10 , a phase shift film 1 formed on the transparent substrate 10 , and a second layer 2 formed on the phase shift film 1 .

[0049] The phase-shift photomask blank of the present invention may include a light-shielding film as a second layer disposed above the phase-shift film. Alternatively, the light-shielding film may be combined with an anti-reflection film to form a second layer. The second layer including the light-shielding film may provide an area that completely blocks the exposure light in the phase-shift photomask. The light-shielding film and the anti-reflection film may also be used as processing auxiliary films in etching. There are many reports on the film structures and materials of the light-shielding film and the anti-reflection film (e.g., JP-A 2007-33469 (Patent Document 2), JP-A 2007-233179 (Patent Document 3)). An example of a preferred film structure in which a light-shielding film and an anti-reflection film are combined is a structure in which a light-shielding film composed of a chromium-containing material is provided, and further an anti-reflection film composed of a chromium-containing material for reducing reflection from the light-shielding film is provided. The light-shielding film and the anti-reflection film may be composed of a single layer or multiple layers. Examples of chromium-containing materials of the light-shielding film and the anti-reflection film include chromium (single substance) and chromium compounds such as chromium oxide (CrO), chromium nitride (CrN), chromium carbide (CrC), chromium oxynitride (CrON), chromium oxycarbon (CrOC), chromium nitride carbide (CrNC), and chromium oxynitride carbide (CrONC). It is worth noting that the chemical formula representing the chromium-containing material only indicates the constituent elements, not the composition ratio of the constituent elements (the same applies to the chromium-containing material below).

[0050] For the second layer as a light-shielding film, or a combination of a light-shielding film and an anti-reflective film, the chromium content of the chromium compound in the light-shielding film is preferably 40 at% or more, more preferably 60 at% or more, and preferably less than 100 at%, more preferably 99 at% or less, and most preferably 90 at% or less. The oxygen content is preferably 60 at% or less, more preferably 40 at% or less, and preferably 1 at% or more. The nitrogen content is preferably 50 at% or less, more preferably 40 at% or less, and preferably 1 at% or more. The carbon content is preferably 20 at% or less, more preferably 10 at% or less, and if the etching rate must be adjusted, it is preferably 1 at% or more. In this case, the total content of chromium, oxygen, nitrogen and carbon is preferably 95 at% or more, more preferably 99 at% or more, and most preferably 100 at%.

[0051] For the second layer as a combination of a light-shielding film and an anti-reflective film, the anti-reflective film is preferably composed of a chromium compound, and the chromium content of the chromium compound is preferably 30 at% or more, more preferably 35 at% or more, and is 70 at% or less, more preferably 50 at% or less. The oxygen content is preferably 60 at% or less, and preferably 1 at% or more, more preferably 20 at% or more. The nitrogen content is preferably 50 at% or less, more preferably 30 at% or less, and preferably 1 at% or more, more preferably 3 at% or more. The carbon content is preferably 20 at% or less, more preferably 5 at% or less, and if the etching rate must be adjusted, it is preferably 1 at% or more. In this case, the total content of chromium, oxygen, nitrogen and carbon is preferably 95 at% or more, more preferably 99 at% or more, and most preferably 100 at%.

[0052] For the second layer as a light-shielding film, or a combination of a light-shielding film and an antireflection film, the thickness of the second layer is generally 20 nm to 100 nm, preferably 40 nm to 70 nm. For exposure light with a wavelength of 200 nm or less, the total optical density of the phase shift film and the second layer is preferably 2.0 or more, more preferably 2.5 or more, and most preferably 3.0 or more.

[0053] A third layer consisting of a single layer or multiple layers may be provided above the second layer of the phase-shift photomask blank of the present invention. The third layer is usually disposed adjacent to the second layer. Specific examples of the third layer are a processing auxiliary film, a light shielding film, and a combination of a light shielding film and an anti-reflection film that functions as a hard mask in the process of patterning the second layer. The material constituting the third layer is preferably a silicon-containing material, in particular a silicon-containing material that does not contain chromium.

[0054] pass Figure 2 This embodiment will be specifically described using the phase shift type photomask blank exemplified in FIG. Figure 2 B is a cross-sectional view illustrating an exemplary phase shift type photomask blank of the present invention. In this embodiment, the phase shift type photomask blank 100 includes a transparent substrate 10, a phase shift film 1 formed on the transparent substrate 10, a second layer 2 formed on the phase shift film 1, and a third layer 3 formed on the second layer 2.

[0055] For the second layer as a light shielding film, or a combination of a light shielding film and an anti-reflection film, a processing auxiliary film (etching mask film) that acts as a hard mask in the process of patterning the second layer can be provided as the third layer. In the case of using the fourth layer as described below, the third layer can be used as a processing auxiliary film that acts as an etching stop layer (etching stop film) in the process of patterning the fourth layer. The processing auxiliary film is preferably composed of a material different from the second layer in terms of etching characteristics, such as a material resistant to chlorine-based dry etching of chromium-containing materials, in particular, a silicon-containing material that can be etched by fluorine-containing gases such as SF6 and CF4. Examples of silicon-containing materials include silicon (single substance) and silicon compounds such as materials containing silicon and any one or two of nitrogen and oxygen, materials containing silicon and transition metals, and materials containing silicon and any one or two of nitrogen and oxygen and transition metals. Examples of transition metals include molybdenum, tantalum and zirconium.

[0056] For the third layer as a processing auxiliary film, the processing auxiliary film is preferably composed of a silicon compound. The silicon content of the silicon compound is preferably 20at% or more, more preferably 33at% or more, and preferably 95at% or less, more preferably 80at% or less. The nitrogen content is preferably 50at% or less, more preferably 30at% or less, and preferably 1at% or more. The oxygen content is preferably 70at% or less, more preferably 66at% or less, and if the etching rate must be adjusted, it is preferably 1at% or more, more preferably 20at% or more. The transition metal content is preferably 35at% or less, more preferably 20at% or less. In this case, the total content of silicon, oxygen, nitrogen and transition metal is preferably 95at% or more, more preferably 99at% or more, and most preferably 100at%.

[0057] For the second layer as a light-shielding film, or a combination of a light-shielding film and an antireflection film, and the third layer as a processing auxiliary film, the thickness of the second layer is generally 20 nm to 100 nm, preferably 40 nm to 70 nm, and the typical thickness of the third layer is generally 1 nm to 30 nm, preferably 2 nm to 15 nm. For exposure light with a wavelength of 200 nm or less, the total optical density of the phase shift film and the second layer is preferably 2.0 or more, more preferably 2.5 or more, and most preferably 3.0 or more.

[0058] For the second layer as a processing auxiliary film, a light shielding film can be provided as the third layer. A light shielding film combined with an anti-reflection film can be provided as the third layer. In this case, the second layer can be used as a processing auxiliary film (etching mask film) that acts as a hard mask in the process of patterning the phase shift film, and as a processing auxiliary film (etching stop film) in the process of patterning the third layer. An example of a processing auxiliary film is a film composed of a chromium-containing material such as disclosed in JP-A 2007-241065 (Patent Document 4). The processing auxiliary film can be composed of a single layer or a multilayer. Examples of chromium-containing materials of processing auxiliary films include chromium (single substance) and chromium compounds such as chromium oxide (CrO), chromium nitride (CrN), chromium carbide (CrC), chromium oxynitride (CrON), chromium carbon oxide (CrOC), chromium nitrogen carbide (CrNC) and chromium oxynitride carbide (CrONC).

[0059] For the second layer as a processing auxiliary film, the chromium content of the chromium compound in the second layer is preferably 40at% or more, more preferably 50at% or more, and preferably 100at% or less, more preferably 99at% or less, and most preferably 90at% or less. The oxygen content is preferably 60at% or less, more preferably 55at% or less, and if the etching rate must be adjusted, it is preferably 1at% or more. The nitrogen content is preferably 50at% or less, more preferably 40at% or less, and preferably 1at% or more. The carbon content is preferably 20at% or less, more preferably 10at% or less, and if the etching rate must be adjusted, it is preferably 1at% or more. In this case, the total content of chromium, oxygen, nitrogen and carbon is preferably 95at% or more, especially 99at% or more, and most preferably 100at%.

[0060] The light shielding film and anti-reflection film as the third layer are preferably composed of a material different from the second layer in terms of etching characteristics, such as a material resistant to chlorine-based dry etching of chromium-containing materials, and in particular, a silicon-containing material such as SF6 and CF4 that can be etched by fluorine-containing gases. Examples of silicon-containing materials include silicon (simple substance) and silicon compounds such as materials containing silicon and either or both of nitrogen and oxygen, materials containing silicon and transition metals, and materials containing silicon and either or both of nitrogen and oxygen and transition metals. Examples of transition metals include molybdenum, tantalum, and zirconium.

[0061] For the third layer as a light-shielding film, or a combination of a light-shielding film and an anti-reflective film, the light-shielding film and the anti-reflective film are preferably composed of a silicon compound. The silicon content of the silicon compound is preferably 10at% or more, more preferably 30at% or more, and preferably less than 100at%, more preferably 95at% or less. The nitrogen content is preferably 50at% or less, preferably 40at% or less, most preferably 20at% or less, and if the etching rate must be adjusted, it is preferably 1at% or more. The oxygen content is preferably 60at% or less, more preferably 30at% or less, and if the etching rate must be adjusted, it is preferably 1at% or more. The transition metal content is preferably 35at% or less, preferably 20at% or less, and preferably 1at% or more. In this case, the total content of silicon, oxygen, nitrogen and transition metal is preferably 95at% or more, more preferably 99at% or more, and most preferably 100at%.

[0062] For the second layer as a processing auxiliary film, and the third layer as a light shielding film, or a combination of a light shielding film and an anti-reflection film, the thickness of the second layer is usually 1 nm to 20 nm, preferably 2 nm to 10 nm, and the thickness of the third layer is usually 20 nm to 100 nm, preferably 30 nm to 70 nm. For exposure light with a wavelength of 200 nm or less, the total optical density of the phase shift film, the second layer and the third layer is preferably 2.0 or more, more preferably 2.5 or more, and most preferably 3.0 or more.

[0063] A fourth layer consisting of a single layer or multiple layers may be provided above the third layer of the phase-shift photomask blank of the present invention. The fourth layer is usually disposed adjacent to the third layer. A specific example of the fourth layer is a processing auxiliary film that functions as a hard mask during patterning of the third layer. The material of the fourth layer is preferably a chromium-containing material.

[0064] pass Figure 2 This embodiment is specifically described by taking the phase shift type photomask blank exemplified in FIG. Figure 2 C is a cross-sectional view illustrating an exemplary phase shift type photomask blank of the present invention. In this embodiment, the phase shift type photomask blank 100 includes a transparent substrate 10, a phase shift film 1 formed on the transparent substrate 10, a second layer 2 formed on the phase shift film 1, a third layer 3 formed on the second layer 2, and a fourth layer 4 formed on the third layer 3.

[0065] For the third layer as a light shielding film, or a combination of a light shielding film and an anti-reflection film, a processing auxiliary film (etching mask film) that functions as a hard mask in the process of patterning the third layer may be provided as a fourth layer. The processing auxiliary film is preferably composed of a material different from the third layer in terms of etching characteristics, such as a material resistant to fluorine-based dry etching of silicon-containing materials, particularly a chromium-containing material that can be etched by an oxygen-containing chlorine-based gas. Examples of chromium-containing materials are chromium (single substance) and chromium compounds such as chromium oxide (CrO), chromium nitride (CrN), chromium carbide (CrC), chromium oxynitride (CrON), chromium oxycarbon (CrOC), chromium nitride carbide (CrNC), and chromium oxynitride carbide (CrONC).

[0066] For the fourth layer as a processing auxiliary film, the chromium content of the fourth layer is preferably 40at% or more, more preferably 50at% or more, and preferably 100at% or less, more preferably 99at% or less, and most preferably 90at% or less. The oxygen content is preferably 60at% or less, more preferably 40at% or less, and if the etching rate must be adjusted, it is preferably 1at% or more. The nitrogen content is preferably 50at% or less, more preferably 40at% or less, and if the etching rate must be adjusted, it is preferably 1at% or more. The carbon content is preferably 20at% or less, more preferably 10at% or less, and if the etching rate must be adjusted, it is preferably 1at% or more. In this case, the total content of chromium, oxygen, nitrogen and carbon is preferably 95at% or more, more preferably 99at% or more, and most preferably 100at%.

[0067] For the second layer as a processing auxiliary film, the third layer as a light shielding film, or a combination of a light shielding film and an anti-reflection film, and the fourth layer as a processing auxiliary film, the thickness of the second layer is usually 1 nm to 20 nm, preferably 2 nm to 10 nm, the thickness of the third layer is usually 20 nm to 100 nm, preferably 30 nm to 70 nm, and the thickness of the fourth layer is usually 1 nm to 30 nm, preferably 2 nm to 20 nm. For exposure light with a wavelength of 200 nm or less, the total optical density of the phase shift film, the second layer and the third layer is preferably 2.0 or more, more preferably 2.5 or more, and most preferably 3.0 or more.

[0068] The film composed of the chromium-containing material for the second layer and the fourth layer can be formed by reactive sputtering using a target such as a chromium target or a chromium-containing target to which one or more elements selected from oxygen, nitrogen and carbon are added, and using a sputtering gas containing a rare gas such as Ar, He and Ne, to which a reactive gas selected from an oxygen-containing gas, a nitrogen-containing gas and a carbon-containing gas is appropriately added according to the composition of the film to be formed.

[0069] At the same time, a film composed of a silicon-containing material for the third layer can be formed by reactive sputtering using a target such as a silicon target, a silicon nitride target, a target containing both silicon and silicon nitride, a transition metal target, a composite target of silicon and a transition metal, and using a sputtering gas containing a rare gas such as Ar, He, and Ne, to which a reactive gas selected from an oxygen-containing gas, a nitrogen-containing gas, and a carbon-containing gas is appropriately added according to the composition of the film to be formed.

[0070] The phase shift photomask of the present invention can be made from a phase shift photomask blank by any conventional method. A phase shift photomask can be made from an exemplary phase shift photomask blank including a film composed of a chromium-containing material formed as a second layer on a phase shift film, generally according to the following process.

[0071] First, an electron beam resist film is formed on the second layer of the phase-shift photomask blank, a pattern is drawn by an electron beam, and then a predetermined development operation is performed to obtain a resist pattern. Next, the obtained resist pattern is used as an etching mask, and the resist pattern is transferred to the second layer by oxygen-containing chlorine-based dry etching to obtain a second layer pattern. Next, the obtained second layer pattern is used as an etching mask, and the second layer pattern is transferred to the phase shift film by fluorine-based dry etching to obtain a phase shift film pattern. In the case where a portion of the second layer needs to be retained, another resist pattern is formed on the second layer to protect the portion to be retained, and the portion of the second layer not protected by the resist pattern is removed by oxygen-containing chlorine-based dry etching. The resist pattern is then removed by a conventional method to obtain a phase-shift photomask.

[0072] A phase-shift photomask can be manufactured from an exemplary phase-shift photomask blank including a light-shielding film or a combination of a light-shielding film and an anti-reflection film made of a chromium-containing material as a second layer on the phase-shift film and a processing auxiliary film made of a silicon-containing material as a third layer on the second layer, typically according to the following process.

[0073] First, an electron beam resist film is formed on the third layer of the phase-shift photomask blank, a pattern is drawn by an electron beam, and then a predetermined development operation is performed to obtain a resist pattern. Next, the obtained resist pattern is used as an etching mask, and the resist pattern is transferred to the third layer by fluorine-based dry etching to obtain a third layer pattern. Next, the obtained third layer pattern is used as an etching mask, and the third layer pattern is transferred to the second layer by oxygen-containing chlorine-based dry etching to obtain a second layer pattern. Then the resist pattern is removed, and the obtained second layer pattern is used as an etching mask, and the second layer pattern is transferred to the phase shift film by fluorine-based dry etching to obtain a phase shift film pattern and remove the third layer pattern at the same time. Next, another resist pattern is formed on the second layer to protect a portion of the second layer to be retained, and the portion of the second layer not protected by the resist pattern is removed by oxygen-containing chlorine-based dry etching. Then the resist pattern is removed by a conventional method to obtain a phase-shift photomask.

[0074] At the same time, a phase-shift photomask can be manufactured from an exemplary phase-shift photomask blank including a processing auxiliary film composed of a chromium-containing material as a second layer on the phase-shift film and a light-shielding film composed of a silicon-containing material as a third layer on the second layer, or a combination of a light-shielding film and an anti-reflective film, generally according to the following process.

[0075] First, an electron beam resist film is formed on the third layer of the phase-shift photomask blank, a pattern is drawn by an electron beam, and then a predetermined development operation is performed to obtain a resist pattern. Next, the obtained resist pattern is used as an etching mask, and the resist pattern is transferred to the third layer by fluorine-based dry etching to obtain a third layer pattern. Next, the obtained third layer pattern is used as an etching mask, and the third layer pattern is transferred to the second layer by oxygen-containing chlorine-based dry etching to obtain a second layer pattern in which the part of the phase shift film to be removed has been removed. Then remove the resist pattern. Next, another resist pattern is formed on the third layer to protect a part of the third layer to be retained, and the obtained second layer pattern is used as an etching mask, and the second layer pattern is transferred to the phase shift film by fluorine-based dry etching to obtain a phase shift film pattern, and simultaneously remove the part of the third layer not protected by the resist pattern. Then remove the resist pattern by a conventional method. Further, remove the part of the second layer exposed to the part where the third layer has been removed by oxygen-containing chlorine-based dry etching to obtain a phase-shift photomask.

[0076] Further, a phase-shift photomask can be manufactured from an exemplary phase-shift photomask blank including a processing auxiliary film composed of a chromium-containing material as a second layer on the phase-shift film, a shading film composed of a silicon-containing material as a third layer on the second layer or a combination of a shading film and an anti-reflection film, and a processing auxiliary film composed of a chromium-containing material as a fourth layer on the third layer, typically according to the following process.

[0077] First, an electron beam resist film is formed on the fourth layer of the phase shift type photomask blank, a pattern is drawn by an electron beam, and then a predetermined development operation is performed to obtain a resist pattern. Next, the obtained resist pattern is used as an etching mask, and the resist pattern is transferred to the fourth layer by oxygen-containing chlorine-based dry etching to obtain a fourth layer pattern. Next, the obtained fourth layer pattern is used as an etching mask, and the fourth layer pattern is transferred to the third layer by fluorine-based dry etching to obtain a third layer pattern. Then the resist pattern is removed. Next, another resist pattern is formed on the fourth layer to protect a portion of the third layer to be retained, and the obtained third layer pattern is used as an etching mask, and the third layer pattern is transferred to the second layer by oxygen-containing chlorine-based dry etching to obtain a second layer pattern, and at the same time, the portion of the fourth layer not protected by the resist pattern is removed. Next, the second layer pattern is used as an etching mask, and the second layer pattern is transferred to the phase shift film by fluorine-based dry etching to obtain a phase shift film pattern, and at the same time, the portion of the third layer not protected by the resist pattern is removed. The resist pattern is then removed by a conventional method. Further, the portion of the second layer exposed in the portion where the third layer has been removed and the portion of the fourth layer exposed in the portion where the resist pattern has been removed are then removed by oxygen-containing chlorine-based dry etching to obtain a phase-shift type photomask.

[0078] When a mask pattern is transferred to a photoresist film formed on a processed substrate by using exposure light with a wavelength of less than 200 nm, such as ArF excimer laser (193 nm) and F2 laser (157 nm), the phase-shift photomask of the present invention is particularly effective in lithography for forming a pattern with a half pitch of less than 50 nm, particularly less than 30 nm, and especially less than 20 nm on the processed substrate.

[0079] The pattern exposure method in the present invention uses a phase shift type photomask manufactured from a phase shift type photomask blank, and irradiates a photomask pattern including a phase shift film pattern with exposure light through the phase shift type photomask, thereby transferring the photomask pattern to a photoresist film, which is formed on a substrate to be processed and is the object of exposure through the photomask pattern. The exposure light can be irradiated by dry exposure or immersion exposure. When the pattern exposure method in the present invention is applied to exposure through the photomask pattern by immersion exposure, which tends to increase the cumulative irradiation energy in a relatively short time in actual production, especially by immersion exposure applied to a wafer with a size of 300 mm or more as a substrate to be processed, the method is particularly effective.

[0080] Example

[0081] Examples of the present invention are given below by way of illustration and not limitation.

[0082] Example 1

[0083] A 6025 quartz substrate of 152 mm square and 6.35 mm thick was placed in a chamber of a sputtering device. A single-layer phase shift film made of SiON was formed on the 6025 quartz substrate using a silicon (Si) target as a sputtering target and argon, nitrogen and oxygen as sputtering gases under the conditions of a power of 1000 W applied to the silicon (Si) target, an argon flow rate of 15 sccm, a nitrogen flow rate of 11 sccm and an oxygen flow rate of 11 sccm, thereby obtaining a phase shift type photomask blank. For ArF excimer laser (193 nm), the phase shift of the phase shift film was 188°, the transmittance was 71% and the thickness was 113 nm. The composition of the film analyzed by XPS (X-ray photoelectron spectroscopy, the same applies hereinafter) was 38 at% silicon (Si), 16 at% nitrogen (N) and 46 at% oxygen (O).

[0084] Example 2

[0085] A 6025 quartz substrate of 152 mm square and 6.35 mm thick was placed in a chamber of a sputtering device, and a single-layer phase shift film made of MoSiON (only the constituent elements are indicated, not the composition ratio of the constituent elements, and the same applies hereinafter) was formed on the 6025 quartz substrate by using a molybdenum silicide (MoSi, indicating only the constituent elements, not the composition ratio of the constituent elements, and the same applies hereinafter) target and a silicon (Si) target as sputtering targets, and argon, nitrogen and oxygen as sputtering gases, under the conditions of 50 W of power applied to the molybdenum silicide (MoSi) target, 1800 W of power applied to the silicon (Si) target, 15 sccm of argon gas flow rate, 20 sccm of nitrogen gas flow rate, and 13.5 sccm of oxygen gas flow rate, thereby obtaining a phase shift type photomask blank. With respect to ArF excimer laser (193 nm), the phase shift of the phase shift film was 185°, the transmittance was 75%, and the thickness was 112 nm. The film had a composition of 37 at% silicon (Si), 15 at% nitrogen (N) and 47 at% oxygen (O) as analyzed by XPS, and a molybdenum (Mo) content ratio (atomic ratio) to the total content of molybdenum (Mo) and silicon (Si) was 0.002, thereby having a molybdenum (Mo) content of less than 1 at%. Although the phase shift film of this embodiment is designed to contain a trace amount of transition metal (Mo), the phase shift film has a phase shift, transmittance and thickness comparable to those of the phase shift film containing no transition metal (Mo) obtained in Example 1.

[0086] Example 3

[0087] A 6025 quartz substrate of 152 mm square and 6.35 mm thick was placed in a chamber of a sputtering apparatus, and a single-layer phase shift film made of MoSiON was formed on the 6025 quartz substrate by using a molybdenum silicide (MoSi) target and silicon (Si) as sputtering targets, and argon, nitrogen and oxygen as sputtering gases, under the conditions of 100 W (which was higher than in Example 2) applied to the molybdenum silicide (MoSi) target, 1,750 W applied to the silicon (Si) target, 15 sccm of argon gas flow rate, 20 sccm of nitrogen gas flow rate, and 16 sccm of oxygen gas flow rate, thereby obtaining a phase shift type photomask blank. The phase shift film had a phase shift of 190°, a transmittance of 74% and a thickness of 130 nm for ArF excimer laser (193 nm). The film has a composition of 36at% silicon (Si), 10at% nitrogen (N) and 53at% oxygen (O) as analyzed by XPS, and the ratio of the molybdenum (Mo) content (atomic ratio) to the total content of molybdenum (Mo) and silicon (Si) is 0.02, thereby having a molybdenum (Mo) content of less than 1at%.

[0088] Comparative Example 1

[0089] A 6025 quartz substrate of 152 mm square and 6.35 mm thick was placed in a chamber of a sputtering apparatus, and a single-layer phase shift film made of MoSiON was formed on the 6025 quartz substrate by using a molybdenum silicide (MoSi) target and a silicon (Si) target as sputtering targets, and argon, nitrogen, and oxygen as sputtering gases, under the conditions of 150 W (which was higher than in Example 3) applied to the molybdenum silicide (MoSi) target, 1,700 W applied to the silicon (Si) target, 17 sccm of argon gas flow rate, 20 sccm of nitrogen gas flow rate, and 18.7 sccm of oxygen gas flow rate, thereby obtaining a phase shift type photomask blank. The phase shift film had a phase shift of 195°, a transmittance of 71%, and a thickness of 152 nm for ArF excimer laser (193 nm). The film has a composition of 34 at% silicon (Si), 5 at% nitrogen (N) and 60 at% oxygen (O) as analyzed by XPS, and the ratio of the molybdenum (Mo) content (atomic ratio) to the total content of molybdenum (Mo) and silicon (Si) is 0.03, thereby having a molybdenum (Mo) content of 1 at%.

[0090] Comparative Example 2

[0091] A 6025 quartz substrate of 152 mm square and 6.35 mm thick was placed in a chamber of a sputtering apparatus, and a single-layer phase shift film made of MoSiON was formed on the 6025 quartz substrate by using a molybdenum silicide (MoSi) target and a silicon (Si) target as sputtering targets, and argon, nitrogen, and oxygen as sputtering gases, under the conditions of 200 W (which was higher than in Comparative Example 1) applied to the molybdenum silicide (MoSi) target, 1,650 W applied to the silicon (Si) target, 15 sccm of argon gas flow rate, 23.5 sccm of nitrogen gas flow rate, and 20 sccm of oxygen gas flow rate, thereby obtaining a phase shift type photomask blank. The phase shift film had a phase shift of 188°, a transmittance of 73%, and a thickness of 160 nm for ArF excimer laser (193 nm). The film has a composition of 32at% silicon (Si), 2.6at% nitrogen (N) and 64at% oxygen (O) as analyzed by XPS, and the ratio of the molybdenum (Mo) content to the total content of molybdenum (Mo) and silicon (Si) (atomic ratio) is 0.04, thereby having a molybdenum (Mo) content of 1at%.

[0092] Comparative Example 3

[0093] A 6025 quartz substrate of 152 mm square and 6.35 mm thick was placed in a chamber of a sputtering device, and a single-layer phase shift film made of SiO was formed on the 6025 quartz substrate by using a silicon (Si) target as a sputtering target, and argon and oxygen as sputtering gases, under the conditions of a power of 1000 W applied to the silicon (Si) target, an argon flow rate of 15 sccm, and an oxygen flow rate of 40 sccm, thereby obtaining a phase shift type photomask blank. For ArF excimer laser (193 nm), the phase shift of the phase shift film was 215°, the transmittance was 90%, and the thickness was 200 nm. The composition of the film analyzed by XPS was 33 at% silicon (Si) and 67 at% oxygen (O).

Claims

1. A phase-shift photomask blank comprising a substrate and a phase-shift film thereon, wherein the phase-shift film is composed of a plurality of layers, wherein the plurality of layers comprises: a layer composed of a transition metal, silicon, nitrogen and oxygen and at least one layer selected from a layer composed of a transition metal, silicon, nitrogen and oxygen and a layer composed of silicon, nitrogen and oxygen, wherein: For light with a wavelength of 200 nm or less, the phase shift of the phase shift film is 150° to 250°, the transmittance is 60% to 80%, the thickness is 150 nm or less, and, The ratio of the content of the transition metal, silicon, nitrogen and oxygen in the layer composed of the transition metal, silicon, nitrogen and oxygen to the total content of the transition metal and silicon is 0.001 to 0.03 in terms of atomic ratio.

2. The phase-shift photomask blank according to claim 1, wherein: The total content of nitrogen and oxygen in each layer constituting the phase shift film is 50 at % or more.

3. The phase-shift photomask blank according to claim 1, wherein: The nitrogen content of each layer constituting the phase shift film is 10 at % or more, and the nitrogen content is lower than the oxygen content in the layer.

4. The phase-shift photomask blank according to claim 1, wherein: The transition metal comprises molybdenum. 5 . The phase-shift photomask blank according to claim 1 , further comprising a second layer consisting of a single layer or a plurality of layers on the phase-shift film, the second layer being composed of a chromium-containing material. 6 . A phase-shift photomask produced by using the phase-shift photomask blank according to claim 1 .

Citation Information

Patent Citations

  • Phase shift mask blank, phase shift mask, and method for manufacturing the same

    JP2007033469A

  • Photomask blank and photomask

    JP2007233179A

  • Photomask blank and photomask

    JP2007241065A

  • Halftone phase shift photomask blank, making method, and halftone phase shift photomask

    CN107868935A

  • Phase Shift Blankmask and Photomask

    KR1020180041042A